2011
DOI: 10.1038/ijir.2011.16
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in women with migraine versus tension-type headaches: a comparative study

Abstract: The aim of this study was to compare the incidence of sexual dysfunction between patients with tension-type headaches (T), migraines (M) and healthy controls (C) in order to investigate the relationship between sexual dysfunction and the features of headaches. The population comprised of 44 patients with M, 30 with T and 30 with C. They have completed Arizona Sexual Experiences Scale (ASEX), Visual Analog Scale. The number of sexual activities over the past 30 days and the frequency of masturbation behavior in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 30 publications
5
20
0
Order By: Relevance
“…Therefore, while it is possible that the associations detected in this study between migraine and ED, and the results reported by previous studies linking migraine to sexual dysfunction in women (8,9), may share neurotransmitter dysregulation as an underlying mechanism, it will be the work of future studies to verify and elucidate these putative underpinnings.…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, while it is possible that the associations detected in this study between migraine and ED, and the results reported by previous studies linking migraine to sexual dysfunction in women (8,9), may share neurotransmitter dysregulation as an underlying mechanism, it will be the work of future studies to verify and elucidate these putative underpinnings.…”
Section: Discussionmentioning
confidence: 61%
“…There are only a few studies examining the relationship between migraine frequency/severity and sexual function. In a recent study by Bestepe et al [4] using the Arizona Sexual Experiences Scale (ASEX), patients with migraine reported higher rates of sexual dysfunction than healthy controls but lower rates than patients with tension type headache while no relationship was detected between the affected domains of sexuality and headache frequency, severity or duration. Similarly, Maizels et al [24] reported that the prevalence of sexual problems among migraine patients were not higher in those experiencing more (number of attacks > 2 days/week) or less frequent attacks.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, university students with migraine had reported more frequent sexual intercourse and reduced sexual satisfaction [3]. In another study, it was found that patients with either migraine or tension type headache experienced a considerable decline in multiple areas of sexuality [4]. This finding was supported in another clinical sample where women with both types of headaches reported high rate s of sexual symptoms and sexual distress [5].…”
Section: Introductionmentioning
confidence: 99%
“…Maizels and Burchette (19) suggested that the frequency of sexual problems in migraine patients did not vary with migraine attack frequency. Similarly, Bestepe et al (20) in their study did not detect a correlation between sexuality and intensity, frequency and duration of headache. In our study, we did not investigate whether intensity, frequency, and duration of headache were correlated with sexual dysfunction.…”
Section: Discussionmentioning
confidence: 93%
“…There are a few studies evaluating the effects of primary headaches that are believed to influence sexual activity and be seen more often in almost all societies on sexual activity (20). The aim of this study was to investigate the frequency of sexual dysfunction in patients having frequent THA.…”
Section: Discussionmentioning
confidence: 99%